FUZZY RELIABILITY EVALUATION OF WEAVING MACHINE IN TEXTILE INDUSTRY - VARGHESE, P. JINI; ROSARIO, G. MICHAEL (International Journal of Mathematical Archive, 2018)
Reliability has vital significance to engineers and designers in Industry. Reliability is a measure of the probability that an item will perform smoothly. In this paper application of fault tree in the industrial systems using trapezoidal intuitionistic fuzzy numbers is presented. The failure rate of weaving machine and the reliability of the system are discussed. Also the concept of trapezoidal intuitionistic fuzzy fault tree analysis is used to find the numerical values.